Study Of Formulation And Performance Characteristics Of Hybrid Biofuel For Compression Ignition Engine Application - Mat, Sharzali Che (2019)
Biofuel from bio-based products such as straight vegetable oil (SVO), bioalcohol and terpenes-rich light biofuel were marked as promising fuel alternative to the fossil fuel. However, each of this biofuel has their own limitation that hinder them from directly been used as an engine fuel. Therefore, this study aims to formulate, optimise, develop and investigate the engine performance, emissions and combustion characteristics of binary and ternary blend of hybrid biofuel as an alternative fuel source for stationary compression ignition (CI) engine. This study introduces a new terpenes-rich light biofuel that is Melaleuca cajuputi oil (MCO) to be blended with refined palm oil (RPO) and hexanol (HX) to produce hybrid biofuel that fully substitute diesel fuel for CI engine applications. The physicochemical properties of neat MCO, RPO and HX were extensively studied to analyses the potential of these biofuel as CI engine fuel. The design of experiments (DOE) approach in the form of mixture design method was adopted to construct the set of experimental runs and to subsequently develop a new prediction model to obtain the optimal hybrid biofuel blend. Spray characteristics of optimise blends were analysed and compared to the diesel fuel. This was followed by developing a test cell system to analyse the performance, combustion, and emission characteristics of optimised hybrid biofuel. Optimised blend of 32RPO68MCO and 35RPO50MCO15HX was found to have the key properties of viscosity, density and calorific value (CV) in accordance to the ASTM D6751/EN14214 standards. Spray characteristics of 35RPO50MCO15HX blend demonstrated comparable spray penetration with maximum different is less than 5% as compared to diesel fuel. Maximum brake power of the engine running with 32RPO68MCO blend were found slightly lower by 8.9% as compared to the baseline diesel fuel. The brake specific fuel consumption (BSFC) of the 32RPO68MCO blend has shown a close resemblance to diesel fuel with the lowest difference of 3.6% occurring at maximum engine load. Notably, at the entire range of test, 35RPO50MCO15HX blend produced lower NOx and smoke opacity as compared to diesel fuel with the maximum reduction of 56.0% and 41.6%, respectively. Overall, this study has shown that hybrid biofuel blend has successfully operated in a diesel engine with a comparable engine performance and exhaust emissions to those of diesel fuel. This shows that the blend is marked as a potential new source of biofuel.